2021
DOI: 10.1088/1361-6560/abd4f9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a coupled simulation toolkit for computational radiation biology based on Geant4 and CompuCell3D

Abstract: Understanding and designing clinical radiation therapy is one of the most important areas of state-of-the-art oncological treatment regimens. Decades of research have gone into developing sophisticated treatment devices and optimization protocols for schedules and dosages. In this paper, we presented a comprehensive computational platform that facilitates building of the sophisticated multi-cell-based model of how radiation affects the biology of living tissue. We designed and implemented a coupled simulation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…Hereby the prediction of cell-survival is the benchmark for testing new models [232]. Going beyond isolated cells to study phenomena such as the radiation induced bystander effect [222] or the radiation response on a tissue level [223] are still in an early stage. However, complete multiscale models including AuNP radiosensitization of DNA into a xenograft mouse model highlight already what can be achieved by integration and combination of simulation and modelling techniques on different scales [258].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hereby the prediction of cell-survival is the benchmark for testing new models [232]. Going beyond isolated cells to study phenomena such as the radiation induced bystander effect [222] or the radiation response on a tissue level [223] are still in an early stage. However, complete multiscale models including AuNP radiosensitization of DNA into a xenograft mouse model highlight already what can be achieved by integration and combination of simulation and modelling techniques on different scales [258].…”
Section: Discussionmentioning
confidence: 99%
“…Their term refers to cells which die or show choromosomal instability without having been directly irradiated during a treatment, as observed by Nagasawa and Little [219] after subjecting Chinese hamster ovary cells (CHO) to low doses of alpha particles, or by Sedelnikova et al which found DSB in bystander cells after irradiation of a human tissue models by a microbeam [220]. To study these effects with a multi-scale approach Geant4 and CompuCell3D [221] were combined by Liu et al via a newly developed bridging module named RADCELL [222]. This allowed them to combined simulations of cell biology and particlescattering simulations to study and quantifying cell behavior after irradiation.…”
Section: Cells and Their Organellesmentioning
confidence: 99%
“…One is the GEANT4-DNA code, a low-energy extension of GEANT4 that enables studies of the cellular radiobiological effects of ionizing radiation on DNA, considering the physical, chemical, and biological stages of the interactions. GEANT4 has also been coupled to the CompuCell3D cell biology simulation platform via the RADCELL module [85], enabling tumor geometries to be ported to the transport code. The ion stopping powers in various materials are key inputs for these codes.…”
Section: Electronics and Human Effectsmentioning
confidence: 99%
“…Outside of plant world other frameworks could be adapted to model plant organs such as CompuCell3D ( Cickovski et al, 2005 ) – a lattice-based multicellular modeling environment to simulate tissue formation by merging the CPM with chemical fields and diffusion equations. CompuCell3D functionalities have been demonstrated in the context of animal embryogenesis, cell population dynamics, tumor formation, and many more ( Andasari et al, 2012 ; Swat et al, 2012 ; Fortuna et al, 2020 ; Liu et al, 2021 ). Another valuable tool to simulate animal embryogenesis is MecaGen, a C++ simulation platform of animal multicellular development relying on mechanistic agent-based models ( Delile et al, 2017 ).…”
Section: Survey Of Mechanical and Biochemical Modeling Frameworkmentioning
confidence: 99%